Good Corporate Governance Affects Company Value with Earnings Management as Intervening Variables in BUMN - Feviana, Dwi Lia; Supatmi, Supatmi (Universitas Pendidikan Ganesha, 2021)
Increasing company value is carried out by management (agents) who manage the company so that it triggers a conflict of interest so that Good Corporate Governance (GCG) is needed. One of the conflicts of interest is practicing earnings management. This study aims to analyze the effect of GCG on firm value mediated by earnings management. The sample used is 19 state-owned companies registered on the Indonesia Stock Exchange in 2017-2019. This study uses SEM-PLS analysis techniques to analyze data. The results showed that GCG had a negative effect on firm value and earnings management. Earnings management does not affect firm value. Earnings management, which is used as an intervening variable, cannot mediate the relationship between GCG and firm value. The limitations in this study are ignoring the variety of industries in BUMN, which may mean that each industry has different policies or practices on GCG and earnings management and different pressures from the market (investors).